Penerapan Model Pembelajaran Kooperatif Tipe Talking Stick Terhadap Pemahaman Konsep Fisika Siswa di MTsN Piladang Kabupaten Lima Puluh Kota - Aswirna, Prima (Universitas Islam Negeri Imam Bonjol Padang, 2018)
This study aims to determine whether the understanding of physics concepts of students taught by using cooperative learning model type of talking stick is better than the understanding of physics concepts taught conventionally in class VII MTsN Piladang District Lima Puluh Kota. The type of this research is quasy experimental research, with the research design of posstest only control group design. The population in this study is class VII MTsN Piladang Year Teaching 2017/2018 consisting of 5 classes. Sampling was done by cluster random sampling technique. Obtained class as experiment class and class as control class. The concept comprehension instrument used in this study is an essay test. Data analysis in this study used t test through SPSS program version 16, because the data is normally distributed and the data group has homogeneous variance. From the research, it is found that the average of experimental class is 80.67 and for the control class is 71.21. Based on data analysis obtained, = 4.027 and = 1.672 at the real level of 0.05. The calculation results show that > , so rejected and accepted. The conclusion obtained that the implementation of Cooperative Type Talking Stick learning model provides a better understanding of the concept of conventional learning model in class VII MTsN Piladang District Lima Puluh Kota